New records of Antarctic and Sub-Antarctic sea anemones (Cnidaria, Anthozoa, Actiniaria and Corallimorpharia) from the Weddell Sea, Antarctic Peninsula, and Scotia Arc - Nielson, M. W. (Zootaxa, 2013)
Herein we provide new records for 22 Antarctic species of sea anemone sensu lato (Anthozoa: Actiniaria and Corallimor-pharia) from theWeddell Sea,Antarctic Peninsula, and theScotiaSea. We provided short descriptions, images of the ex-ternal morphology of preserved specimens (but also of living specimens in most cases), cnida data, and distribution maps for each studied species. New records are presented for nine species in theWeddell Sea and the geographic or bathymetric distributions for 19 of the 22 studied species are extended.